(untitled) (Research, Society and Development, 2022)
Stroke is a disease responsible for 5 million permanent disabilities, causing changes according to the affected location and extent, these changes result in deficits in functional capacity, motor, cognitive, balance, coordination, speech, sensitivity and may also affect swallowing, causing dysphagia. The study aims to demonstrate the presence of dysphagia in the elderly after the occurrence of stroke. The present research is an integrative literature review, carried out from July to August 2022, through electronic searches in the Google Scholar database, with articles published in electronic format in the period between 2012 and 2012 being defined as inclusion criteria. 2021, available for free in Portuguese and that help in the discussion on the subject. Thus, 2200 scientific articles were found and of these only 10 meet the inclusion criteria and research objectives. According to the results found, changes in swallowing can be commonly found after the occurrence of a stroke, which can lead to impairment of pharyngeal motor dysfunction and delay in the initiation of swallowing, some other changes such as in the laryngeal closure mechanism are found, where about 50% of post-brain accident patients have dysphagia. Therefore, it is concluded that dysphagia ends up affecting the elderly public, being mainly related to the aging of the structures and due to some underlying pathology, such as stroke.